PARP1-NFATc1-PD1 pathway of maturation and stability of CD8+T cells is beneficial against chronic Trypanosoma cruzi infection - Imran H. Chowdhury; Nandadeva Lokugamage; Nisha J. Garg (iScience, 2025)
Summary: Poly(ADP-ribose) polymerase 1 (PARP1) inhibition improved the ventricular function in Chagas disease (CD). Here, we uncovered that Parp1 depletion enhances cardiac health by regulating CD8+T cell response against Trypanosoma cruzi (Tc) infection. For this, Parp1−/− and wild-type (WT) mice were challenged with Tc and euthanized at acute and chronic phases of parasite replication and CD development, respectively. Parp1−/− mice controlled the chronic parasite persistence and associated inflammatory pathology more effectively than WT mice. Parp1−/− enhanced the maturation and stability of metabolically reprogrammed CD8+ effector and memory T cells with increased cytotoxic effects against the parasite. Mechanistically, PARP1 depletion enhanced the NFATc1 translocation to Pdcd1 promoter in CD8+T cells, altered the PD1:PDL1 stoichiometric ratio between CD8+T and antigen-presenting cells, and promoted CD8+T cell longevity and function during chronic Tc infection. We conclude that molecular and chemical inhibitors of PARP1 would offer a potential therapy to arrest CD pathogenesis.